OPTIMIZATION OF ROBOT MANIPULATOR MOTION ADAPTED FOR CONVEYOR PROCESSES - Toshpulatov Qobil Yaxyoxon ogli (Web of Journals Publishing, 2024)
This article addresses the challenges and solutions for optimizing the motion of robotic manipulators used in industrial conveyor systems. Conveyor manufacturing processes require high precision and efficiency, which can be enhanced by optimizing the robot manipulators' movements. By refining the movement trajectories, planning sequences, and adjusting control algorithms, it is possible to improve operational efficiency, reduce time, and conserve energy. This study discusses methods of trajectory calculation, motion sequence planning, and speed-parameter adjustments for optimal robot control in conveyor settings. The article concludes with an analysis of the results achieved through optimization and the technologies applied.
Keywords: Robot manipulator, conveyor systems, motion optimization, industrial automation, motion trajectory, energy efficiency, control algorithms.